2023
DOI: 10.1038/s41416-023-02145-w
|View full text |Cite
|
Sign up to set email alerts
|

Proactive breast cancer risk assessment in primary care: a review based on the principles of screening

Abstract: In the UK, the National Institute for Health and Care Excellence (NICE) recommends that women at moderate or high risk of breast cancer be offered risk-reducing medication and enhanced breast screening/surveillance. In June 2022, NICE withdrew a statement recommending assessment of risk in primary care only when women present with concerns. This shift to the proactive assessment of risk substantially changes the role of primary care, in effect paving the way for a primary care-based screening programme to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 112 publications
0
7
0
Order By: Relevance
“…A recent review determined that breast cancer risk assessment for women under 50 years currently satisfies many of the key principles for screening 20. However, uncertainties remain with respect to the optimal strategy for implementation and potential impact of the invitation process on health inequalities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review determined that breast cancer risk assessment for women under 50 years currently satisfies many of the key principles for screening 20. However, uncertainties remain with respect to the optimal strategy for implementation and potential impact of the invitation process on health inequalities.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review determined that breast cancer risk assessment for women under 50 years currently satisfies many of the key principles for screening. 20 However, uncertainties remain with respect to the optimal strategy for implementation and potential impact of the invitation process on health inequalities. The Breast CANcer Risk Assessment in Younger women (BCAN-RAY) case–control study (NCT05305963) aims to evaluate a comprehensive breast cancer risk assessment strategy among a diverse ethnic and socioeconomic population of women aged 30–39 years without a strong family history of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Parallel to the development of LB applications in preventive medicine, AI was used to identify an increasing degree of health problems in various segments of the population for a novel cycle of screening programs, including the targeted screening and stratified screening [ 3 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the United States suggested that it is feasible to conduct a risk assessment of a patient during the time when a patient is waiting meet their doctor [ 61 , 62 ]. Coordination is needed regarding further genetic testing and the initiation of risk-reducing medication by specialists such as oncologists and breast surgeons [ 63 ]. On a more positive note, primary healthcare in Malaysia has been shown to provide comprehensive, coordinated, and continuity of care in private and public sectors [ 64 ].…”
Section: Introductionmentioning
confidence: 99%